From competition to collaboration: Unraveling teachers’ lesson study experiences - Romiro G. Bautista; Wilfredo B. Baniqued (International Journal of Evaluation and Research in Education (IJERE), 2021)
Lesson study is a professional development program among teachers. It reciprocates teachers’ development to students’ outcomes. It is also an act of leveraging classroom practices, enriching teachers’ content knowledge, and process skills and beliefs. This study explored the experiences of a group of science secondary school teachers that implemented the lesson study in their classes. Qualitative data were gathered from the informants’ interview during the implementation of the lesson study. Data were processed through document trail among the informants to ascertain the veracity of the transcribed responses, reflections, and observations. Thematic analysis revealed five themes on the experiences of the teachers in implementing the Lesson Study: developing a culture of oneness, crafting teachers’ competence through synergism, boosting teachers’ morale and confidence, refining the quality of the research lesson, and scheming avenues for critical thinking. It is, therefore, suggested that lesson study be implemented by all teachers across all subject-areas in the division and introduced among pre-service teachers to further discover its efficacy towards teachers’ development and students’ outcomes. Furthermore, it is strongly suggested that knowledgeable others be involved in the implementation of the lesson study as their presence were found significant in ensuring its success as most of the teachers are not specialized in the field that they are teaching.